PENGORGANISASIAN PENGOLAHAN SAMPAH DESA SANGEH, KABUPATEN BADUNG, PROVINSI BALI: waste treatment, oganisasi, principle of organization, the organization - Prasetyo, Andika Hijrah; Githa Girindra, Ida Ayu (JAMAK, 2018)
The waste problem in indonesia now has already been conveyed to the stage of an emergency. If this is not dealt with immediately so can result in disaster. There should have been the act of and special attention from the government to the problem. The community should also actively assisting the government played a role. According to on ministry of environmental and forestry data in the year 2017 indonesia produced garbage around 187,2 million tons per year. Sangeh Village, Kecamatan Abiansemal, Badung District, Bali, there are waste treatment plant and equipment that organic waste management can be like dung. Unfortunately the most of facility yet to be fully developed by the village community because of a lack of understanding as well as concern for trash processing. Based on this it is necessary to stipulate a body or an organization that effectively be able to manage waste treatment plant one that was already available that fulfills the 5 organization (personal, cooperation, the purpose, the environment and resources). And in running an organization must be based on principle of management (planning organization, organizing, staffing, directing, coordinating, reporting, budgeting). This paper focuses on the analysis of organizing waste processing